Riis, sentimentalitet og byreform - Holm Vogelius, Christa (K&K - Kultur og Klasse, 2021)
This paper examines the work of Danish-American photojournalist Jacob Riis through the lens of sentimentality and racial ethics. While Riis’s use of sentimental appeals is often overlooked or dismissed as insignificant by modern critics, these tactics reveal essential aspects of his racial and national reform project. Riis, I argue, is heir to mid-nineteenth century theories of racial evolution that blended Lamarckism and Darwinism, figuring personal and racial transformation as a process that could take place through environmental influence; such pre-eugenic theories were a subtext in a range of sentimental literature, including notably mid-nineteenth century to early twentieth century writing and reform efforts in Manhattan’s tenement districts. Riis’s reflections on the Lower East Side in landmark works such as How the Other Half Lives (1890) and The Children of the Poor (1892) are deeply inflected by the conventions of sentimentality, and his writing, like other reform work of the time, frames children as uniquely susceptible to the positive or negative effects of environment, an understanding that shapes his view of the developing American nation.